The Evaluation of National Development: Approaches Based on the Budgetary Planning Framework - Bolaños Garita, Rolando (2014)
Successful performance of public budgets inexorably forces to understand the scheme of national development planning, which should be formed by political, administrative, legal and conceptual dimensions that sustain and shape to it. Therefore, any assessment would be distorted and does not add value to public budget resources, if it does not understand these dimensions first, and activate the series of mechanisms and actions of governmental direction established in the Constitution and other laws. Then, the achievement of national development may crystallize as long as the executive and legislative branches have a clear notion of this scheme, and put their skills to work around or over the key factors of policy direction and political control, respectively.